2016
DOI: 10.1097/md.0000000000004749
|View full text |Cite
|
Sign up to set email alerts
|

Sleep time and pattern of adult individuals in primary care in an Asian urbanized community

Abstract: Sleep norms vary between individuals, being affected by personal, communal, and socioeconomic factors. Individuals with sleep time which deviate from the population norm are at risks of adverse mental, cardiovascular, and metabolic health. Sleep-related issues are common agenda for consultation in primary care. This study aimed to determine the sleep time, pattern, and behavior of multiethnic Asian individuals who attended public primary care clinics in an urban metropolitan city-state.Standardized questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
5
1
Order By: Relevance
“…This observation is line with survey data showing that developed Asian nations such as Japan, South Korea, and Singapore have the shortest sleep times internationally, at just under 7.5 hours a night (Walch et al 2016). Separate local studies have found that 44% of adult visitors to local clinics have insufficient sleep on weekdays (Tan et al 2016), and that the prevalence of poor sleep (PSQI > 5) in Singapore is approximately 1 in 4 (Tan et al 2017). These figures notwithstanding, a higher-than-expected 63/96 of our participants reported PSQI scores greater than 5 at baseline, suggesting that poor sleepers were self-selecting into either the mindfulness program or our research study.…”
Section: Subjective Sleep Quality Improved In Both Experimental Groupssupporting
confidence: 87%
“…This observation is line with survey data showing that developed Asian nations such as Japan, South Korea, and Singapore have the shortest sleep times internationally, at just under 7.5 hours a night (Walch et al 2016). Separate local studies have found that 44% of adult visitors to local clinics have insufficient sleep on weekdays (Tan et al 2016), and that the prevalence of poor sleep (PSQI > 5) in Singapore is approximately 1 in 4 (Tan et al 2017). These figures notwithstanding, a higher-than-expected 63/96 of our participants reported PSQI scores greater than 5 at baseline, suggesting that poor sleepers were self-selecting into either the mindfulness program or our research study.…”
Section: Subjective Sleep Quality Improved In Both Experimental Groupssupporting
confidence: 87%
“…8 Our findings concerning smoking and insufficient sleep are consistent with findings from other studies which reported that sleep-deprived individuals tend to smoke and have caffeinated drinks two hours before bedtime. 28,29 Our findings differ from past evidence that young adults are more vulnerable to chronic sleep deficiency and recurrent circadian disruption than older adults, 30 and are at odds with reports which indicate that older adults are less likely to experience issues related to sleep. 22 The presence of children has been found to be a risk factor for insufficient sleep among adults.…”
Section: What Is Already Knowncontrasting
confidence: 99%
“… 8 Our findings concerning smoking and insufficient sleep are consistent with findings from other studies which reported that sleep-deprived individuals tend to smoke and have caffeinated drinks two hours before bedtime. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations